Taman Botani Boyolali Dengan Pendekatan Fun Design Sebagai Pusat Wisata Edukasi Botani - Atika Dwi Harjanti; Ofita Purwani; Tri Yuni Iswati (Regional Development Information Center, Universitas Sebelas Maret, 2017)
Boyolali is one city in Indonesia with a massive growth in infrastucture development, especially in terms of public and communities space development that became urban planning goals of Boyolali city in the last five years. There are many development programs that have been planned by the goverment, one of them is the plan for building Botanical Garden as a conservation area and public space in 2016. This program is the reason why Boyolali Botanical Garden is choosen as the object design. The design of the Botanical Garden is more focused on the educational recreation purpose that implement fun learning experiences as a learning method. This method has proven to make learning new things, in this case is botany , fun and easier to understand. The architectural approach used to solve the design problems of this Botanical Garden is Fun Design approach, so the design of Botanical Garden tries to direct architectural elements toward a design that gives a pleasant and fun environment to the users because fun environment is the most conductive learning climate for non-formal education. The architectural elements that can help to form a fun environment in Fun Design approach is : Forms, Mass Arragement, Colors, Materials, Aperture and Lighting. These elements can help to create a fun learning environment by emphasizing the design decision on the impression that can be conveyed by each elements. The impression that need to be conveyed by the design to make fun learning environment among others is cheerfullness, energetic, happy, flexible, freedoom, and refreshing. One of the example is the application of bright color (such as yellow, red, blue, ect) to convey cheerfulness and energetic impression on the design.